Upacara-Upacara dalam Budaya Masyarakat Banten - Siti Fauziyah (Tsaqofah, 2016)
Before Islam, Banten residents as residents in areas in the archipelago has a great tendency to things spiritual. Once Islam became the religion professed, Banten community still has a great tendency toward mysticism. Once thickened Banten society with matters related to religious ceremonies that are grown in culture Banten people always can not be separated from religious elements.Ceremonies in Banten culture continued, albeit ranging changes occur due to the constantly changing with the times. Ceremonies performed by the Banten community not only as an effort to preserve the ancestral culture but also able to build social solidarity for the culprit.